Hardware Comparison of Schedulers for Modular Optical Interconnection Networks - Borromeo, J C (Archīum Ateneo, 2019)
We present the first FPGA implementation of the Two-Step Scheduler framework for modular optical interconnection networks. The longest-queue-first scheduling algorithm guarantees the lowest latency, while the iSLIP algorithm minimizes the hardware resources and scheduling duration.